EFFECTS OF AROMATHERAPY MASSAGE ON THE SLEEP QUALITY AND PHYSIOLOGICAL PARAMETERS OF PATIENTS IN A SURGICAL INTENSIVE CARE UNIT - Özlü, Zeynep Karaman; Bilican, Pınar (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Surgical pain is experienced by inpatients with clinical, disease-related concerns, unknown encounters after surgery, quality of sleep, restrictions in position after surgery is known to be serious. The study was conducted to determine the effect of aromatherapy massage on quality of sleep and physiological parameters in surgical intensive care patients. Materials and Methods: This is an experimental study. The sample of this study consisted of 60 patients who were divided into two groups as experimental group and control group including 30 patients in each one. The participants were postoperative patients, absent complications, who were unconscious and extubated. A data collection form on personal characteristics of the patients, a registration form on their physical parameters and the Richards-Campbell Sleep Scale (RCSQ) were used to collect the data of the study. Results: The Richards-Campbell Sleep Scale indicated that while the experimental group had a mean score of 53.80 ± 13.20, the control group had a mean score of 29.08 ± 9.71 and there was a statistically significant difference between mean scores of the groups. In a comparison of physiologic parameters, only diastolic blood pressure measuring between parameters in favor of an assembly as a statistically significant difference was detected. Conclusions: Results of the study showed that aromatherapy massage enhanced the sleep quality of patients in a surgical intensive care unit and resulted in some positive changes in their physiological parameters.